16th Topical Meeting on the Optics of liquid Crystals - Parka, Janusz; Klosowicz, Stanislaw (Photonics Letters of Poland, 2015)
The current issue of the Photonics Letters of Poland contains 5 selected papers presented during the 16th Topical Meeting on the Optics of Liquid Crystals, which was held from September 13 to 18, 2015 in Sopot, Poland. The remaining 8 papers included in the issue are regular contributions.